Effect of Emotional Intelligence and Self-Confidence on Accounting Understanding - Febyanti, Mutiara; Kurniawan, Agus (Journal of Islamic Finance and Economic Studies, 2025)
Background: A good understanding of accounting is essential for accounting students, as it impacts their ability to perform as accountants in the professional world. Factors such as emotional intelligence and self-confidence are believed to influence accounting comprehension. This study aims to examine the effect of emotional intelligence and self-confidence on accounting understanding among accounting students. Aims: This research aims to analyze the effect of emotional intelligence and self-confidence on accounting understanding among accounting students. Methods: This study employs a quantitative approach, using primary data collected through questionnaires distributed to accounting students. Data analysis was performed using multiple linear regression to examine the influence of emotional intelligence, self-confidence, and accounting understanding. Results: The analysis results indicate that both emotional intelligence and self-confidence do not have a significant effect on accounting understanding among students. The significance value in the t-test was greater than 0.05, leading to the rejection of the hypothesis that these variables positively affect accounting understanding. Additionally, simultaneous testing showed no significant influence between both variables and accounting understanding. Conclusion: Based on the results, it can be concluded that emotional intelligence and self-confidence do not have a significant impact on accounting understanding among accounting students. However, other factors not explored in this study may have a larger effect on students' accounting comprehension.